Association between isolated abnormal levels of maternal serum unconjugated estriol in the second trimester and adverse pregnancy outcomes - Thaniyaporn Settiyanan (2018)
© 2015 Taylor & Francis. Objective: To determine the association between maternal serum unconjugated estriol (uE3) levels in the second trimester and adverse pregnancy outcomes.Patients and methods: The prospective database of our fetal Down screening program was assessed and reviewed for maternal serum uE3 levels. Pregnancies with medical diseases, abnormal levels of beta-human chorionic gonadotropin, alpha-fetoprotein and fetal chromosomal or structural abnormalities were excluded. The recruited women were categorized into three groups: high (>95th percentile), normal (5-95th percentile) and low (<5th percentile) uE3 levels.Results: Of 14 212 screened women, 9183 (high; 455, normal; 8271 and low; 457) levels group, were available for outcome analysis. The rates of most adverse outcomes, including preterm birth, low Apgar scores, fetal death, placental abruption, preeclampsia and gestational diabetes mellitus, of the high and normal groups were comparable. Nevertheless, low uE3 levels increased risk of fetal growth restriction (FGR) (RR: 2.36, 95% CI: 1.79-3.10) and low birth weight (LBW) (RR: 1.87, 95% CI: 1.45-2.39), but not preterm birth. Logistic regression analysis indicated that low uE3 level was an independent risk factor for FGR and LBW.Conclusions: High uE3 levels in the second trimester are not associated with poor outcomes, whereas low levels significantly increase risk of FGR and LBW but not other adverse outcomes.